THE ROLE OF PHYSICAL CONDITION AS THE BASIS FOR IMPROVING THE PERFORMANCE OF AMPUTEE FOOTBALL ATHLETES AT PERSAS SURABAYA CLUB - Wahyono, Muhammad; Nuryadi , Achmad; Mardhika, Riga; Hakim, Luqmanul; Irfan Majid, Ahmad; Arya Murtadha, Dzakka; Maria De Ligouri Kristiyanto Andaru , Alfonsus (Antis-publisher, 2025)
Objective: This study aimed to enhance the athletic performance of amputee soccer players from PERSAS Surabaya through structured physical tests and awareness of a healthy lifestyle. The focus was on measurable training programs, nutrition, and rest to improve performance and immunity. Method: The program was conducted by the Physical Education team from Universitas PGRI Adi Buana Surabaya. The activities included planning, coordination with the PERSAS club management, designing physical tests, conducting simulations, socialization, and implementing the tests. A total of 15 athletes and 2 coaches participated. Results: The physical test results provided a foundation for developing tailored training programs. Emphasis on well-planned training schedules, proper nutrition, and adequate rest was identified as crucial for performance improvement. Novelty: This program uniquely addressed the specific needs of amputee soccer players by integrating comprehensive physical testing and emphasizing a holistic approach to health and fitness, which is rarely explored in similar contexts.